4CPS-261 The role of adherence to lipid-lowering therapies in achieving lipid target: findings from real-world analysis. (23rd March 2022) - Degli Esposti, L; Borghi, C; Galvani, M; Giacomini, E; Manotti, P; Marra, A; Passaro, A; Perrone, V; Pieraccini, F; Sangiorgi, D; Navazio, A
Abstract : Background and importance: A high level of adherence to lipid-lowering drugs has been associated with a decreased morbidity and mortality among patients in cardiovascular (CV) disease prevention.[1] Aim and objectives: The objective of the present real-world analysis was to evaluate the impact of adherence to lipid-lowering drugs in reaching the lipid target in settings of clinical practice in Italy. Material and methods: The analysis was based on the administrative and laboratory database of selected healthcare units in Italy covering approximately 10% of the Italian population. Adult patients prescribed with statin and with at least a low-density lipoprotein (LDL) determination were included between 2012 and 2019. The index date was defined as the first prescription for statin within the inclusion period. Patients fell into four clusters collectively exhaustive and mutually exclusive based on their characteristics assessed during the year prior to the index date. Patients were considered as adherent if they had a proportion of days covered (PDC) ≥80%. Results: Among overall patients prescribed statin and with a LDL determination, 1% was with familial hypercholesterolemia, 28% with previous cardiovascular events, 21% with diabetes and 50% in primary prevention. Regardless of their risk profile, the increasing of adherence was related to a higher achievement of LDL-target, with an increment of +53.2% in familial hypercholesterolaemia, +43.1% in diabetes and +30% in previous cardiovascular events and primary prevention clusters while progressing from low (PDC <40%) to high (PDC ≥80%) levels of adherence. However, while in the diabetes and primary prevention clusters 80% and 86% of adherent patients, respectively, had their cholesterol level under control, in the familial hypercholesterolaemia and previous cardiovascular events clusters only 46% of adherent patients achieved the lipid target. Conclusion and relevance: The analysis showed adherence to be a key factor for cholesterol control. However, our findings underline a therapeutic need for patients that, although adherent, fail to achieve the lipid target, especially among patients with previous cardiovascular events (that have a low level of LDL to achieve) and with familial hypercholesterolemia (that have a high LDL basal level), suggesting therapeutic intensification should be applied. References and/or acknowledgements: 1. McGinnis B, et al. Factors related to adherence to statin therapy. Ann Pharmacother 2007;41 :1805–11. Conflict of interest: No conflict of interest